Religion, Education and Power Related During The Government of Andi Sultan Daeng Radja in The Kingdom of Gantarang Bulukumba - Muhammad Saleh Tajuddin; Ihwana As’ad; Andi Tenri Yeyeng (Vox Populi, 2022)
This paper discusses the relationship between religion, education and power during the reign of Andi Sultan Daeng Radja in the Gantarang Bulukumba Kingdom. The type of research used is qualitative with a political, historical and theological approach. Primary and secondary data were obtained through observation, interviews, documentation and reference searches in the form of textbooks and scientific journals. The analysis used is the analysis of Miles and Haberman through the following steps: data presentation, data verification and drawing conclusions. The results obtained from the research include: 1) The relationship between religion and power in the Gantarang Bulukumba Kingdom experienced a golden age during the reign of Andi Sultan Daeng Radja, because he was a figure who really cared about religious issues that were integrated with power. 2) Some of Andi Sultan's successes during his reign, including: building a grand mosque, maximizing religious activities, Education and politics at the at-Taqwa Ponre mosque, and establishing a Muhammadiyah organization and a Muhammadiyah Islamic school in Gantarang which other kingdoms participated in.